Prevalence of hypertension and cardiovascular risk factors among long‐term AIDS survivors: A report from the field. Issue 10 (26th August 2019) - Pierre, Samuel; Seo, Grace; Rivera, Vanessa R.; Walsh, Kathleen F.; Victor, Jean Joscar; Charles, Benedict; Julmiste, Gaetane; Dumont, Emelyne; Apollon, Alexandra; Cadet, Molene; Saint‐Vil, Alix; Marcelin, Adias; et al.
Abstract: HIV infection is associated with increased risk and progression of cardiovascular disease (CVD), yet little is known about the prevalence of CVD risk factors among long‐term AIDS survivors in resource‐limited settings. Using routinely collected data, we conducted a retrospective study to describe the prevalence of CVD risk factors among a cohort of HIV‐infected patients followed for over 10 years in Port‐au Prince, Haiti. This cohort includes 910 adults who initiated antiretroviral therapy (ART) between 2003 and 2004 and remained in care between 2014 and 2016 when routine screening for CVD risk factors was implemented at a large clinic in Haiti. A total of 397 remained in care ≥10 years and received screening. At ART initiation, 59% were female, median age was 38 years (IQR 33‐44), and median CD4 count was 117 cells/mm 3 (IQR 34‐201). Median follow‐up time from ART initiation was 12.1 years (IQR 11.7‐12.7). At screening, median CD4 count was 574 cells/mm 3 (IQR 378‐771), and 84% (282 of 336 screened) had HIV‐1 RNA < 1000 copies/mL. Seventy‐four percent of patients had at least 1 risk factor including 58% (224/385) with hypertension, 8% (24/297) diabetes, 43% (119/275) hypercholesterolemia, 8% (20/248) active smoking, and 10% (25/245) obesity. Factors associated with hypertension were age (adjusted OR 1.06, P  < .001) and weight at screening (adjusted OR 1.02, P  = .019). Long‐term AIDS survivors have a high prevalence of CVD risk factors, primarily hypertension. Integration of cardiovascular screening and management into routine HIV care is needed to maximize health outcomes among aging HIV patients in resource‐limited settings.